Large-Volume Lateral Lymph Node Metastasis Predicts Worse Prognosis in Papillary Thyroid Carcinoma Patients With N1b - Gao, Luying; Li, Xiaoyi; Xia, Yu; Liu, Ruifeng; Liu, Chunhao; Shi, Xinlong; Wu, Yanjiao; Ma, Liyuan; Jiang, Yuxin (Frontiers in Endocrinology, 2022)
We aimed to evaluate the relevance of large-volume lateral lymph node metastases (LLNMs) at risk of recurrence/persistence in papillary thyroid carcinoma (PTC) with LLNMs (N1b). This retrospective study included 448 PTC patients, who had positive LLNMs confirmed by histology and suspected of LLNMs by preoperative ultrasound. According to the number of pathological LLNMs, patients were divided into large-volume LLNM (number of LLNMs >5) and low-volume LLNM (number of LLNMs ≤5). Risk factors of recurrence/persistence in PTC patients with N1b were analyzed. Preoperative ultrasound features of PTC with large-volume LLNM were analyzed. For the patients with a mean follow-up of 44.0 months, the risk of recurrence/persistence was 25.1% in PTC patients with N1b. The recurrence/persistence rate was significantly higher in patients with large-volume LLNM than in patients with low-volume LLNM by multivariate analysis (37.3% vs. 17.1%; HR=2.451, 95% CI 1.41-4.261, P=0.001). The 3-year and 5-year recurrence/persistence -free survival for those with large-volume LLNM were 93.2% and 47.2%, respectively. Moreover, we found that multilevel suspected LLNMs and loss of fatty hilum were independent preoperative indicative factors of large-volume LLNM (OR=6.239, 95% CI 3.547-10.977, P <0.001; OR=5.149, 95% CI 1.859-14.261, P = 0.002). In conclusion, multilevel suspected LLNM and loss of fatty hilum on ultrasound tended to be more common in patients with large-volume LLNM. PTC patients with large-volume LLNM are at a higher recurrent/persistent risk than those with low-volume LLNM. Large-volume LLNM may be used to stratify the risk of recurrence/persistence in PTC.